Implementation of Web-Based Regional Innovation Selection Process Automation: A Case Study of Pasuruan Regency - Firza Prima Aditiawan; Agung Mustika Rizki; Eva Yulia Puspaningrum (SINTA Journal (Science, Technology, and Agricultural), 2025)
Digital transformation in the regional innovation selection process is key to improving transparency, efficiency, and accountability. To encourage an innovation ecosystem in Pasuruan Regency, Bappelitbangda held the Pasuruan Maslahat Technology Innovation Competition with three categories: (1) Regional Innovation (governance/public services), (2) Technological and Non-Technological Innovation, and (3) Learning Innovation. The main challenges of the competition are the high volume of proposals, process traceability, and consistency of assessment. This article presents the design and implementation of the Maslahat Innovation and Technology Selection Website system to automate the end-to-end flow: registration, proposal upload, administrative verification, multi-reviewer assessment, weighted score aggregation, nomination determination, and publication of results. The three-layer web-based architecture is designed with role control (admin, secretariat, reviewer, participant, public), audit trail, and proportional information disclosure policy. The assessment method uses Simple Additive Weighting (SAW) with min–max normalization and weighting per category. The expected outcome is improved operational efficiency, accountability, and transparency of the selection process so that the sustainability of the competition can be ensured.